2009
DOI: 10.2967/jnumed.108.059162
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Cyclosporine Inhibition of P-Glycoprotein Activity Using 11C-Verapamil in the Brain: Studies of Healthy Humans

Abstract: The multiple-drug resistance (MDR) transporter P-glycoprotein (P-gp) is highly expressed at the human blood-brain barrier (BBB). P-gp actively effluxes a wide variety of drugs from the central nervous system, including anticancer drugs. We have previously demonstrated P-gp activity at the human BBB using PET of 11 C-verapamil distribution into the brain in the absence and presence of the P-gp inhibitor cyclosporine-A (CsA). Here we extend the initial noncompartmental analysis of these data and apply compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(159 citation statements)
references
References 22 publications
8
151
0
Order By: Relevance
“…To relate flux to measurable quantities, we rely upon the methods described by Sokoloff for deoxyglucose, and for the moment, ignore the small contribution of de-phoshorylation (k 4 ). Under Steady state conditions for the native substance, the exchangeable compartment content, Qe, is constant, and thus (5) Re-arranging terms yields (6) For the native substance, TdR, the blood concentration is constant. Referring to the constant native compound concentration as [TdR] and substituting for CpFLT, the flux equation now becomes (7) The fraction term describes what is often termed the flux constant, Ki, which is a macro parameter (a combination of rate parameters), that appear in the flux term as a rate constant describing the overall flow of the tracer from the blood, through the metabolic pathway and into the retained compartment Qm: (8) In the analysis of FLT model parameter error, sensitivity and accuracy, we find that the parameters that are the most well defined are transport of the tracer, K 1 , and overall metabolic flux, Ki, and are also of the most biological interest as well.…”
Section: Interpretation Of Flt Model Parametersmentioning
confidence: 99%
“…To relate flux to measurable quantities, we rely upon the methods described by Sokoloff for deoxyglucose, and for the moment, ignore the small contribution of de-phoshorylation (k 4 ). Under Steady state conditions for the native substance, the exchangeable compartment content, Qe, is constant, and thus (5) Re-arranging terms yields (6) For the native substance, TdR, the blood concentration is constant. Referring to the constant native compound concentration as [TdR] and substituting for CpFLT, the flux equation now becomes (7) The fraction term describes what is often termed the flux constant, Ki, which is a macro parameter (a combination of rate parameters), that appear in the flux term as a rate constant describing the overall flow of the tracer from the blood, through the metabolic pathway and into the retained compartment Qm: (8) In the analysis of FLT model parameter error, sensitivity and accuracy, we find that the parameters that are the most well defined are transport of the tracer, K 1 , and overall metabolic flux, Ki, and are also of the most biological interest as well.…”
Section: Interpretation Of Flt Model Parametersmentioning
confidence: 99%
“…23 However, because (R)-[ 11 C]-verapamil is a low-extraction radiotracer, its uptake is considered insensitive to changes in cerebral blood flow. 10 In addition, Muzi et al 8 reported that the CS modulation of Pgp increased the blood-brain transfer of (R)- [ 11 C]-verapamil into the brain by 73%, and this increase was significantly greater than changes in blood flow by 13%.…”
Section: Fig 2 T1-weighted Mr Images (Axial Viewmentioning
confidence: 99%
“…8 Participants underwent a 60-minute PET scan after an intravenous injection of 370 MBq of (R)-[ 11 C]-verapamil radiotracer (range, 333-407 MBq). Simultaneous acquisitions of 3D dynamic PET images and T1-weighted MR images were performed by using a Biograph mMR (Siemens, Erlangen, Germany).…”
Section: Pet/mr Imaging and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The microconstants can also be used to calculate macroparameters such as 'distribution volume' (DV) of the probe. The compartmental approach has been applied to data of therefore, almost all of the effect attributed to P-gp is the decrease in K 1 (block the entry of the radioligand to the intracellular compartment) (27,37). Importantly, because blood flow influences the initial transfer of many probes into tissues, transport (K1) may be normalized by flow.…”
Section: Quantification Of Imaging Datamentioning
confidence: 99%